Team Writing for Team Building: A Collaborative Writing Approach for Use in Traditional and Online Classrooms of English Language Learners - Aixa Perez-Prado (Asociación Colombiana de Profesores de Ingles, 2017)
This article explores the possibilities of team writing for team building activities in classes of second language learners. Both face-to-face and online collaborative writing activities are discussed. These activities stem from a whole language approach to literacy acquisition including process writing and other interactive collaborations among learners. Team writing for team building activities include the characteristics of cooperation and collaboration among learners, the use of the four language skills, peer editing and reviewing, publication and display, both online and offline are presented. A step-by-step detailed example of one such activity is given, for use either in the classroom or through distance learning.